THE EVOLUTION OF THE LITERARY GENRE OF SCIENCE FICTION - Yuldasheva Mahinur Baxodir qizi; Raxmatova Iqbol Isroil qizi; ABDURAMONOVA DIANA VALERYEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: The development of science fiction as a literary genre involves a rich interplay between imaginative storytelling and societal reflection. This article explores the historical evolution of science fiction, tracing its roots from early mythologies and 19th-century speculative fiction to modern interpretations. Key movements, such as Golden Age science fiction and the New Wave, are highlighted for their transformative impact on narrative structure, themes, and social commentary. Additionally, the article delves into how technological advancements and cultural shifts have influenced the genre,  providing  a  lens  through  which  to  understand  its  profound  relevance.  By examining notable works and authors, the article articulates how science fiction not only entertains but also challenges our understanding of reality, ethics, and the future. Ultimately, it positions science fiction as a vital genre that mirrors the complexities of human experience and imagines possibilities beyond current boundaries.